The Relationship Between Sharia Audit and Compliance with Islamic Financial Principles - Monika Handayani; Herlian Maulana (Citakonsultindo, 2025)
The role of sharia auditors is increasingly important in ensuring compliance with Islamic finance principles, especially in line with the rapid development of the sharia finance industry. Sharia auditors not only check the conformity of transactions with sharia principles, but also provide recommendations to improve financial institution policies and procedures. Financial products such as sukuk, murabahah financing, mudharabah and musharakah require careful supervision so as not to violate sharia principles, such as the prohibition of usury and excessive uncertainty. The challenges in ensuring compliance are increasingly complex with differences in fatwa interpretation in various countries and the use of financial technology (fintech) in Islamic finance. Sharia audits also play an important role in maintaining transparency, accountability and strengthening the internal control systems of Islamic financial institutions. In addition, sharia audits support the development of sharia capital markets and the credibility of sharia investment products. Through a more dynamic role, sharia audit is not only an evaluation tool, but also an educational tool that strengthens the culture of sharia compliance in sharia financial institutions.